Analisis Logam Timbal (Pb) Dan Besi (Fe) Dalam Air Laut Di Pelabuhan Desa Paranggi Kecamatan Ampibabo - Fiskanita, Fiskanita; Hamzah, Baharuddin; Supriadi, Supriadi (Universitas Tadulako, 2015)
Determination of concentration of lead (Pb) and iron (Fe) has been conducted in sea water in Paranggi village, district of Ampibabo. The method used is spectrophotometry, namely atomic absorption spectrophotometer (AAS). Sea water sample is taken in the morning with a 3-point sampling, which is at a distance of Â± 5 m, 10 m and 15 m respectively. The 3-point sampling is from the port side of the back end of the ship and the port end of the backrest ship at a distance of Â± 5 m ahead. Analysis of Pb level is measured at a wavelength of 217 nm and Fe at a wavelength of 248.3 nm. Result shows that Pb levels at point A is 0.4869 mg/L, at point B is 0.5304, and at point C is 0.4869 while for the Fe levels shows that at point A is 0.3073, at point B is 0.2652, and at point C is 0.2863. The range of the concentration of Pb is between 0.4869 to 0.5304 mg/L. This concentration is higher when compared with the NAB Pb, 0.025 mg/L. Furthermore, the range of the concentration of Fe is from 0.2652 to 0.3073 mg/L. Similarly to Pb result above, this concentration is higher when compared with the NAB Fe, 0.01 mg /L.